Shaping Future Leaders: A Bibliometric Study on Leadership Development (West Science Interdisciplinary Studies, 2025)
Leadership development has attracted growing scholarly attention in response to rapid technological change, sustainability challenges, and evolving workforce dynamics; however, the expanding body of literature remains fragmented across disciplines and perspectives. This study aims to map the global research landscape of leadership development through a bibliometric analysis of publications indexed in the Scopus database, using VOSviewer to examine publication trends, keyword co-occurrence, citation patterns, and collaboration networks among authors, institutions, and countries. The results show that leadership constitutes the central intellectual core of the field, closely linked to organizational management, interpersonal communication, decision making, education, and professional development, while more recent research increasingly emphasizes themes such as artificial intelligence, sustainability, innovation, and visionary leadership. The analysis also reveals a highly collaborative and internationally connected research community, with strong contributions from North America and Europe and growing cross-regional partnerships. Overall, this study provides a systematic overview of the intellectual structure and evolutionary trajectory of leadership development research, offering a useful reference for scholars and practitioners in identifying dominant themes and emerging directions for shaping future leaders⁠.